Turkey : 2004 Article IV Consultation and Eighth Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance of Performance Criterion-Staff Reports; Staff Supplement; Public Information Notice and Press Release of the Executive Board Discussion; and Statement by the Executive Director for Turkey. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper examines Turkey's 2004 Article IV Consultation and Eighth Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance of Performance Criterion. Economic performance over the last three years has been impressive. For the medium term, the main challenge is to implement policies that achieve the goals of sustained growth and low inflation. The authorities need to take steps to encourage foreign direct investment, to make good on their plans for privatization, and to reform the judicial system to facilitate the functioning of Turkey's market economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet